2016
DOI: 10.1002/pen.24294
|View full text |Cite
|
Sign up to set email alerts
|

A new protocol for accelerated screening of long-term plasticity-controlled failure of polyethylene pipe grades

Abstract: In this study, a new experimental protocol to evaluate long‐term, plasticity‐controlled failure using short‐term testing is validated on a high‐density polyethylene (PE100) pipe grade. The protocol starts with the assessment of the strain rate dependence of the yield stress in uniaxial extension at various temperatures. Additional uniaxial compression tests are performed to characterize the influence of hydrostatic stress. The plastic flow kinetics are subsequently captured using a Ree‐Eyring modification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 48 publications
2
59
1
Order By: Relevance
“…All curves in Figure a demonstrate a strict power‐law behavior with a slope −1, indicating that each curve is well described by a single value of critical strain, irrespective of the occurrence of progressive aging. It should be noted that we observe a considerable variation in the critical strain as a function of temperature; similar observations were made on other semicrystalline polymers like PE . Hence, to improve the lifetime predictions, the critical strain has been optimized for each temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All curves in Figure a demonstrate a strict power‐law behavior with a slope −1, indicating that each curve is well described by a single value of critical strain, irrespective of the occurrence of progressive aging. It should be noted that we observe a considerable variation in the critical strain as a function of temperature; similar observations were made on other semicrystalline polymers like PE . Hence, to improve the lifetime predictions, the critical strain has been optimized for each temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that we observe a considerable variation in the critical strain as a function of temperature; similar observations were made on other semicrystalline polymers like PE. [49] Hence, to improve the lifetime predictions, the critical strain has been optimized for each temperature. This allows the description of the time-tofailure under static load including the evolution of the thermodynamic state by effectively integrating Equation (12) where the plastic strain rate evolves as a result of temperature and stress induced progressive aging until the critical strain is reached (see solid drawn lines in Figure 19d):…”
Section: Lifetime Predictions and Endurance Limit Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In eq 36, p a is the hydrostatic pressure of the amorphous phase. Kanters et al 24 compared this approach with one that involves separate kinematics for the two relaxation processes and found that there is only a small difference between the aforementioned approaches.…”
Section: Amorphous Phase Constitutive Modelmentioning
confidence: 99%